Predictive factors regarding bullying behavior in Romanian schools - Rus, Mihaela; Călin, Mariana Floricica; Sandu, Mihaela Luminița; Tasențe, Tănase (Frontiers in Psychology, 2024)
From the age point of view, we have had n=210 12-year-old subjects and 193 13-year-old subjects, and from the biological gender point of view, there were 234 girls and 169 boys. The study's main objective was to investigate aggressive behavior in adolescents in a school context. The study is cross-sectional and aims to analyze behaviors and interpersonal relationships having as dependent variable "Conflicts in the school environment" and two independent variables, respectively "Aggressive Manifestations" and "Aggressive Behaviors", used in proving the first hypothesis, dependent variable "Verbal attacks as an aggressor" and the predictive variables "Social exclusion" and "Conflicts within the school environment" used to demonstrate the second hypothesis and the dependent variable "Bullying behavior" and the predictor variables "Acceptance of unethical behaviors", "Violation of privacy as an aggressor" and "Dissemination of information without authorization" used to demonstrate the third hypotheses.The results indicate significant correlations between aggressive behaviors and conflicts in the school environment (r=0.596, p<0.001), suggesting that interventions must be integrated and address the underlying causes of aggressive behaviors and associated manifestations. The association between "Conflicts in the school environment" and "Aggressive behaviors" revealed a significant correlation (r=0.387, p<0.001) and a moderate correlation between "Perception of conflicts" and "Aggressive manifestations" (r=0.423, p<0.001).The conclusions emphasize the importance of understanding the complexity of aggressive behavior dynamics and predictive factors for developing effective strategies for prevention and intervention in the educational environment. As a limitation of the study, it is advisable to follow the group of subjects from a longitudinal point of view to identify changes in the behavioral manifestations of these adolescents, in a school context.